Asymmetric Catalytic Approach to Multilayer 3D Chirality. Issue 30 (1st May 2021) - Wu, Guanzhao; Liu, Yangxue; Rouh, Hossein; Ma, Liulei; Tang, Yao; Zhang, Sai; Zhou, Peng; Wang, Jia‐Ying; Jin, Shengzhou; Unruh, Daniel; Surowiec, Kazimierz; Ma, Yanzhang; et al.
Abstract: Invited for the cover of this issue is Guigen Li and co‐workers at Texas Tech University and Nanjing University. The cover artwork shows that chirality phenomena exists in the universe and in nature, including at micro and molecular levels. Read the full text of the article at 10.1002/chem.202100700 . Abstract : " Here, we discuss a new form of chirality, multilayer 3D chirality. This work presents the first asymmetric catalytic approach to multi‐layer 3D chirality and shows that one of the aromatic rings of phosphorous oxide can be a parallel plane of this chirality ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 8013 ff. (DOI: 10.1002/chem.202100700 ).